The impact of collaborative transportation management on demand disruption of manufacturing supply chains - Li, Jing; Chan, Felix T.S. (International journal of production research, 2012)
This paper describes the impact of collaborative transportation management (CTM) on the performance of manufacturing supply chains using a multi-agent approach. Two supply chain models (with and without CTM) are proposed to show how it realises the real operational interactions between different supply chain partners under demand disruption. Simulation results of the proposed models reveal the evolution of the CTM supply chain with demand disruption. The dynamic delivery ability and order point which are caused by demand disruption in the CTM supply chain are investigated. The results indicate that CTM can significantly reduce costs and improve the flexibility of companies in handling demand disruption problems. It is suggested that CTM is an efficient mechanism to manage supply chains, especially under a demand disruption environment.